ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) RISK RATINGS AND FIRM MARKET VALUE - Handajani, Lilik; Sokarina, Ayudia; Husnan, Lalu Hamdani (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study aims to analyze the impact of ESG risk ratings on market performance metrics, proxied by Earnings per Share (EPS) and Tobin’s Q. Multiple regression analysis was conducted using 85 company-year observations of firms consistently included in the IDX ESG Leaders Index during the 2020–2024 period. The results indicate that firms with lower ESG risk are more highly valued by the market, as reflected in higher EPS. However, ESG risk ratings do not have a significant effect on firm market value as measured by Tobin’s Q, suggesting that investor stock valuations remain more focused on short-term financial indicators rather than long-term ESG risk management. These findings imply that ESG risk management should be aligned with the objective of sustaining strong short-term financial performance. Strong financial performance, in turn, enhances firms’ capacity to manage environmental, social, and governance risks more effectively.